An exploratory study of Type B variation of the sciatic nerve - Rehir, Rasyidah; Teoh, Jun Mun; Chan, Sumar; Almansour, Raghad Abdulaziz; Alshaya, Abeer Saleh; Alashkham, Abduelmenem (Frontiers in Neurology, 2025)
BackgroundSciatic nerve gives off branches that supply the back of the thigh, leg, and foot. Classically, this nerve emerges from the greater sciatic foramen below the piriformis muscle and subsequently divides into the common fibular and tibial nerves in the distal third of the posterior thigh. However, the course of the sciatic nerve varies among individuals, potentially resulting in nerve compressions. Understanding these variations helps prevent injuries during diagnostic and therapeutic procedures. This study examined the branching patterns of this nerve in the Scottish cadavers using the Beaton and Anson classification, which categorizes them into Type A–G.MethodsTwelve gluteal regions (4 males, 8 females) with a mean age of 87.3 years, were obtained from a Scottish University regulated by the Human Tissue (Scotland) 2006. The sciatic nerve and its branches were carefully dissected, and the relationship between the nerve and the piriformis muscle was observed and documented.ResultsOne left gluteal region of an 89-year-old female (n = 1, 8.3%) showed sciatic nerve variation. This variant exhibited early bifurcation, with the common fibular nerve piercing through the piriformis and the tibial nerve passing beneath it (referred to as Type B). The remaining 91.7% of cases, the sciatic nerve exhibited classical presentation (referred to as Type A).ConclusionThe Type B variation of the sciatic nerve is found in 8.3% of the elderly Scottish cadavers. While it is rare, it is crucial to acknowledge nerve variants to prevent injuries during posterior approach total hip arthroplasty or inadequate sciatic nerve blockade.